Ecology of algal mats and their role in the formation of stromatolites in Antarctic dry valley lakes - Wharton, Robert A. (Virginia Polytechnic Institute and State University, 1982)
Algal mats comprised primarily of Phormidium frigidum Fritsch, Lyngbya martensiana Menegh., and several species of pennate diatoms are found in the below-ice benthic regions of Lakes Bonney, Chad, Hoare, Fryxell, and Vanda, southern Victoria Land, Antarctica. Mats are also found in the littoral moats and ice-covers of several lakes, and in cryoconite holes on Canada Glacier. Variations in temperature, light, oxygen, salinity, and nutrient levels between lakes and different habitats in the same lake result in differences in species composition, morphology, biomass, and photosynthetic pigment content of the mats. Algal mats are trapping and binding sediment, and precipitating minerals, particularly calcite. Mats are removing organic and inorganic matter from the arheic lakes via transfer through the icecovers or by incorporation into the sediments. Some of the algal mats are laminated, organosedimentary structures and can be considered stromatolitic. Depending upon ambient and subsequent environmental conditions non-columnar, columnar, and pinnacle-shaped stromatolites are forming, some of which are partially lithified. If environmental variables (i.e. low light intensity, lack of burrowers or browsers, and relative lack of turbulence) associated with these stromatolites do not vary significantly, it is probable that they may result in a lacustrine carbonate sedimentary deposit. Ph. D.